2023
DOI: 10.3389/fphar.2023.1100556
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy and safety of pyrotinib in patients with HER2-positive metastatic breast cancer: A prospective real-world study

Abstract: Background: Pyrotinib, a novel irreversible EGFR/HER2 dual tyrosine kinase inhibitor, shows encouraging anticancer activity and acceptable tolerability in multiple phase II and phase III randomized clinical trials, but the real-world data of pyrotinib, especially the outcomes in HER2-positive metastatic breast cancer, have been rarely reported. Here, we evaluated the treatment outcomes of pyrotinib in real-world practice in patients with HER2-positive metastatic breast cancer (MBC).Methods: This was a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The study revealed that the ORR and DCR of our group were 56% and 75%, respectively. The median time for PFS and OS in our group was 16 months 35 months.And our treatment outcomes were consistent with another latest study, .In that prospective trial of 113 patients with HER-2 positive MBC, the median PFS was 14.1 months with an ORR of 66.4% [25].There was no statistical signi cance for the PFS and OS of patients received combined chemotherapy with pyrotinib and pyrotinib mono-therapy, which indicated the signi cant role of pyrotinib mono-therapy in the treatment of HER-2 positive MBC to reduce the nancial burden of those patients.…”
Section: Discussionsupporting
confidence: 91%
“…The study revealed that the ORR and DCR of our group were 56% and 75%, respectively. The median time for PFS and OS in our group was 16 months 35 months.And our treatment outcomes were consistent with another latest study, .In that prospective trial of 113 patients with HER-2 positive MBC, the median PFS was 14.1 months with an ORR of 66.4% [25].There was no statistical signi cance for the PFS and OS of patients received combined chemotherapy with pyrotinib and pyrotinib mono-therapy, which indicated the signi cant role of pyrotinib mono-therapy in the treatment of HER-2 positive MBC to reduce the nancial burden of those patients.…”
Section: Discussionsupporting
confidence: 91%
“…Results from the phase 3 PHOEBE (36) and PHENIX (23) studies have shown the favorable effects of pyrotinib in patients with HER2-positive MBC after trastuzumab. The PERMEATE trial (24), subpopulation analysis of the PHENIX trail (23), and retrospective real-world studies (22,37) showed the activity with pyrotinib against BM. Our study investigated the real-world data of pyrotinib in patients with BM at baseline in complicated clinical practice and supplemented the findings of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies, which enrolled patients partially receiving PyroC therapy, have shown improvement in survival with the use of Pyro‐based regimens as first‐line treatment for HER2‐positive mBC. 19 , 20 However, the evidence level is not convincing enough. For instance, Yin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some retrospective studies, which enrolled patients partially receiving PyroC therapy, have shown improvement in survival with the use of Pyro-based regimens as first-line treatment for HER2-positive mBC. 19,20 However, the evidence level is not convincing enough. For instance, Yin et al reported that mPFS was 20.9 months for patients receiving first-line Pyro treatment, which enrolled only 28 patients, partially treated by PyroC.…”
Section: Introductionmentioning
confidence: 99%